Characterizing exposure of veterans to Agent Orange and other herbicides used in Vietnam : final report (Online access: NCBI NCBI Bookshelf., 2003)
The intent of the present report is to summarize briefly the work done by the contractor over the life of the study and to serve as a vehicle for cataloging and transmitting that work to VA. The sections below delineate the work of the Columbia University researchers as it evolved from proposal through delivery. It is based on the material provided by the Columbia University researchers in their 6-month progress reports, presentations, draft materials, and final report; and it quotes freely and extensively from these materials.